SOCIO-PSYCHOLOGICAL FEATURES OF THE FORMATION OF A SCIENTIFIC WORLDVIEW AMONG STUDENTS - Razakov Farkhod Kuvondikovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article describes the socio-psychological features of the formation of the scientific age of students and the necessary conditions for the formation of mental education in them.